Enzymatic Synthesis Of Olive-based Ferulate Esters: Optimization By Response Surface Methodology - Salina Mat Radzi; Nurul Jannah Abd Rahman; Hanina Mohd Noor; N. Ariffin (Open Science Research Excellence, 2024)
Volume: 8 No:8